Exogenous carbon source and phytohormone supplementation enhanced growth rate and metabolite production in freshwater microalgae Scenedesmus obtusus Meyen. (June 2021) - Vijay, Aravind K.; Salim, Said Ali M.; Prabha, Syama; George, Basil
Abstract: In the present work, indigenous freshwater microalga Scenedesmus obtusus Meyen was isolated and cultivated under supplementation of additional carbon sources and phytohormones to improve its biomass yield and metabolite production. Optimum concentration of bicarbonate has resulted in 1.4 fold increase in biomass yield along with higher carbohydrate and protein content. Meanwhile increased lipid content (32.9% dry cell weight) with higher neutral lipid proportion (62–66%) was evident under acetate supplementation. Among the tested phytohormones, kinetin exhibited 1.6 fold increase in biomass productivity at 25 μM concentration. Higher concentration (>50 μM) of indole-3-acetic acid have incited significant increase in lipid and carotenoid content. The results indicates that the S. obtusus can efficiently utilise the supplemented carbon source for higher biomass production and also favourably modulate its metabolite productivity in response to the supplemented phytohormones. Graphical abstract: Unlabelled Image Highlights: Carbon and phytohormones improved microalgal growth at optimum concentrations. Bicarbonate addition improved carbohydrate and protein content in S. obtusus . Supplementation of acetate increased biomass yield and lipid content in S. obtusus . IAA at 100 μM enhanced carotenoid and neutral lipid content in S. obtusus . Kinetin as low-cost biostimulant can improve the feasibility of mass cultivation.